2015
DOI: 10.17860/efd.15447
|View full text |Cite
|
Sign up to set email alerts
|

Türk Eğitim Sistemindeki FATİH Projesinin Çevre, Girdi, Ürün, Süreç Modeline Göre Analizi

Abstract: Türkiye 2000'li yıllardan günümüze eşitlikçi bir sistem kurma alanında önemli kazanımlar elde ederek "FATİH Projesi"yle yenileşme sürecine girmiştir. Proje; teknoloji kullanımı yoluyla, eğitimde fırsat eşitliğinin her toplumsal katmanda sağlanmasına yönelik bir girişimdir. Bu araştırma, FATİH Projesi uygulamalarında görev alan öğretmen ve yöneticiler olmak üzere 200 katılımcıyla Projenin CIPP modeline göre incelenerek Türkiye şartlarına uygun olup olmadığının ortaya çıkarılması amacına yönelik olarak gerçekleş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…In one of the other studies conducted within the scope of the FATIH project (Ekici & Yılmaz, 2013), it was stated that there are some problems in the analysis, implementation, and result parts of the project. In another study (Karabacak, 2015), it was stated that there are some problems related to the CIPP headings of the project. On the other hand, in another study (Dinçer et al, 2013), it was indicated that there is no sufficient cooperation with universities within the scope of the project and that teachers have several deficiencies although they show positive attitude toward the project.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the other studies conducted within the scope of the FATIH project (Ekici & Yılmaz, 2013), it was stated that there are some problems in the analysis, implementation, and result parts of the project. In another study (Karabacak, 2015), it was stated that there are some problems related to the CIPP headings of the project. On the other hand, in another study (Dinçer et al, 2013), it was indicated that there is no sufficient cooperation with universities within the scope of the project and that teachers have several deficiencies although they show positive attitude toward the project.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…In a study conducted by Karabacak (2015), the FATIH project was evaluated according to the context, input, process, and product (CIPP) model. As a result of that study, it was discovered that problems such as software components, use of information and communication technology in curricula, educational e-content, in-service training, and conscious information and communication technology use are encountered in the "context" dimension of the project; problems such as the determination of instructional strategies, methods, and techniques that will be used in the e-content are encountered in the "input" dimension.…”
Section: Studies On the Evaluation And Analysis Of The Fatih Projectmentioning
confidence: 99%
“…Sarıtepeci, Durak ve Seferoğlu (2016) öğretmenlerin öğretim teknolojileri alanında hizmet-içi eğitim gereksinimlerini inceledikleri çalışmada, çalışma grubundaki öğretmenlerin çoğunluğunun "FATİH Projesi Eğitimde Teknoloji Kullanımı Kursu" başlıklı hizmetiçi eğitim etkinliklerine katılmalarına karşın eğitimde teknoloji kullanımı, internetin eğitim amaçlı kullanımı ve öğretim araç gereçlerini etkin kullanma konularından gereksinimlerinin karşılanamadığını ortaya koymaktadır. Bunun gibi daha birçok çalışmada (Ayvacı, Bakırcı ve Başak, 2014;Baz, 2016;Ekici ve Yılmaz, 2013;Karabacak, 2015;Karatekin, Elvan ve Öztürk, 2015;Kocaoğlu ve Akgün 2015;Koçak, 2013;Kurtdede Fidan, Erbasan ve Kolsuz, 2016;Özdemir, 2014;Türker ve Güven, 2016) da benzer sorunlara değinilmiştir. Kısacası Türkiye'de eğitim teknolojilerine yapılan yatırımlar sayesinde okulların BİT donanımları artırılmakta ve hizmetiçi eğitimler geliştirilmekte, ancak dijital bölünme konusunda öğretmen ve öğrenci görüşleri henüz yeterince dikkat çekmemektedir.…”
Section: Introductionunclassified